Groundwater Pollution by Petroleum Hydrocarbons Resulting from Vehicle Washing, Lubrication, and Oil Change Activities in the City of Ajilat: A Field Study (Al-Farooq Journal of Sciences, 2026)
This study aims to assess the impact of liquid waste (petroleum hydrocarbons) from car wash and oil change stations in the Al-Ajilat area on groundwater quality for various uses. Eight groundwater samples were collected and analyzed from wells located within the immediate geographical range of the stations. Tests were conducted using a HORIBA OCMA-500 instrument to determine the total hydrocarbon (TPH) concentrations.The results showed that all studied sites suffered from hydrocarbon pollution exceeding safe limits, with concentrations ranging from 0.5 to 17.3 mg/L. The comparative analysis revealed that stations attached to fuel stations recorded the highest pollution levels at a concentration of 17.3 mg/L, which is several times higher than the concentrations recorded at stations that only wash and change oil.